1990
DOI: 10.1007/bf02171565
|View full text |Cite
|
Sign up to set email alerts
|

Total parenteral nutrition associated cholestasis: A predisposing factor for sepsis in surgical neonates?

Abstract: Abstract.Of 496 neonates and infants less than i year of age admitted to the paediatric surgical intensive care unit (PSICU) over a 5 year period (1983)(1984)(1985)(1986)(1987), 94 required total parenteral nutrition (TPN) for more than 14 consecutive days, generally due to congenital anomalies of the digestive tract. Cholestasis occurred in 15 of them and 12 of these patients developed sepsis. In contrast, of the 79 patients on TPN that remained free from cholestasis, only 23 developed sepsis. The mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Others have reported higher frequencies, that is, 67% [12] and 62.5% [16]. Earlier research of our study group showed that only 16% of 94 neonates and infants (b1 year old) who required PN for more than 14 days developed PN-related cholestasis [23]. This condition is probably associated with multiple risk factors including prematurity, immature hepatic function, lack of enteral feeding, sepsis, and various toxicities or deficiencies in PN [24].…”
Section: Discussionmentioning
confidence: 86%
“…Others have reported higher frequencies, that is, 67% [12] and 62.5% [16]. Earlier research of our study group showed that only 16% of 94 neonates and infants (b1 year old) who required PN for more than 14 days developed PN-related cholestasis [23]. This condition is probably associated with multiple risk factors including prematurity, immature hepatic function, lack of enteral feeding, sepsis, and various toxicities or deficiencies in PN [24].…”
Section: Discussionmentioning
confidence: 86%
“…Bloodstream infections are the most common severe complication of PN (20). Numerous strategies have been attempted to prevent the risk of PN‐related sepsis with different successes (21–23). Our data suggest that continuing enteral nutrition in feed‐intolerant patients results in a more rapid advancement of feeding, which in turn determines a reduced time to reach full enteral nutrition and the duration of PN (11).…”
Section: Discussionmentioning
confidence: 99%
“…Bile stasis may predispose to sepsis, [81][82][83] possibly by impairing cell-mediated immunity. 84 Sepsis occurred in 80% of infants with PNAC compared with 29% of infants without cholestasis (p=0.006).…”
Section: Effects Of Bile Stasis On Sepsismentioning
confidence: 99%
“…84 Sepsis occurred in 80% of infants with PNAC compared with 29% of infants without cholestasis (p=0.006). 82 Although a high frequency of sepsis was reported in patients with PNAC, further studies are necessary to clarify the effects of cholestasis on sepsis.…”
Section: Effects Of Bile Stasis On Sepsismentioning
confidence: 99%